A computational study of the actuation speed of the hydraulic cylinder under different portsâ sizes and configurations - Abdalla, M.O. (Taylor's University, 2015)
The discharged oil from hydraulic cylinder, during its operation, is highly restricted by the small sized outlets. As a result, a back pressure builds up and the piston motion, therefore, is slowed down; the system pump has to do additional work to overcome this hydraulic resistance so as to preserve the required speed. In this study the possibility of improvement of the actuation speed of the hydraulic cylinders was investigated and analysed. Both a four-port cylinder and a resized-ports cylinder were proposed as fast cylinders. FLUENT 6.3 was used for the simulation of the oil flow field of the hydraulic cylinders. Results showed that relation between discharge flow and the outlets diameters is best described by a power law having coefficients partially depending on the system pressure. It had also shown that for any given total outlet area, the actuation speed of the single outlet cylinders is always higher than that of the double outlets cylinders. In one case where the total outlet area is 3.93E-05m2, the actuation speed of the single outlet cylinder is 21 higher than that of the double outlets cylinder; whereas, when doubling the total outlet area the different is reduced to just 6. Resizing the outlet for small ports was more efficient than using multi-outlets; while for a large ports it shows no significant difference to use either one outlet port or multi-outlets. Both the solutions of resizing or ports addition need special valve to be fit to the cylinder so that the cylinder could be effectively operated under the control of the proportional valve. Â© School of Engineering, Taylorâs University